RELATIONSHIP BETWEEN PARENTS, PEER, LECTURER ATTACHMENT AND ISLAMIC RESILIENCY AMONG UNIVERSITY PUTRA MALAYSIA STUDENTS - Hannina HALIMATUSAADIAH HAMSAN (AL-FIKRA, 2016)
The main purpose of this study is to determine  the relationship  between parents, peer, lecturer attachment and resiliency among UPM students. Three factors which are parents, peer and lecturer attachment have been studied about their relationship with resiliency. A total of 397 undergraduates students in UPM were selected through convenience sampling as respondents in this study. Inventory of Parents and Peer Attachment  (Armsden  and  Greenberg,  1987)  was  used  to  measure  the  level  of parents  and  peer  attachment,  followed  by Inventory  of Teacher-Student Relationships (Murray and Zvoch, 2011) to measure the level of lecturer attachment and Adolescent  Resilience  Scale (Oshio,  Kaneko,  Nagamine  & Nakaya,  2003)  to assess the level of students’ resiliency. The results of this study show that most of the respondents perceived moderate level of resiliency (M = 78.18; SD = 7.697), peer attachment (M = 101.27; SD = 13.283) and lecturer attachment (M = 45.46; SD =9.096), and high level of parents attachment (M = 103.22; SD = 11.495). The findings revealed  that  there  was  significant  relationship  between  parents  attachment  (r  =0.434; p = 0.000), peer attachment (r = 0.455; p = 0.000), lecturer attachment (r =0.495; p = 0.000) and resiliency. The result from the study shows that the importance of improving the level of resiliency among the students in university is increasing the attachment  to students’  parents,  peer,  and lecturer  in order  to become  the good student in the life.